The incidence of employment subsidies for vocational training - Albaek, Karsten [Verfasser] (My University, 2012)
"This paper analyses employment subsidies for vocational training under union wage bargaining. The analysis includes an investigation of the consequences of financing the subsidy by a levy on employment, which is the typical way of financing these types of subsidies in many countries. The paper demonstrates high incidence rates of subsidies for vocational training under standard assumptions about the preference structure of the union. The financing scheme appears to counteract the purpose of the subsidy." (Autorenreferat, BIBB-Doku)
Keywords: S 2.2.2 Regelung der betrieblichen Ausbildung; S 4.1.4 Fonds- und Umlagefinanzierung; S 4.2.1 Personalkosten; Betriebliche Berufsausbildung; Ausbildungsplatzförderung; Modell; Lohnkostenzuschuss; Ausbildungsplatzabgabe; Tarifvertrag; Gewerkschaft; Ausbildungsvergütung; Einkommenshöhe